AN ECONOMETRIC ANALYSIS OF IMPACTS OF EXCHANGE RATES ON IMPORTS: AN EMPIRICAL STUDY ON SRI LANKAN CONTEXT - Mustafa, A.M.M.; Nisthar, S. (University of Jaffna, 2019)
This study aims to find out the relationship between the trends of various exchange rates and the trend of imports on Sri Lankan empirical context. The quantitative method is used by using the time series data in this study. The annual time series data used in this study are collected from the annual report of Central Bank of Sri Lanka for the time periods from year 1950 to year 2017. The multiple regression model is used to find out the impact of the independent variables such as Indian Rupees, Japanese Yen, Pound Sterling, and US Dollar on the dependent variable such as imports of Sri Lanka. The Granger Causality Test is used to find out the causal relationship among all the variables. The Johansen Co-Integration Test is used to find out long run equilibrium relationship among the variables. Pound Sterling of United Kingdom and Dollar of United Statesare positively impacts on the Imports of Sri Lanka. Indian Rupees and Japanese Yen are inversely associated with the imports. According to the Granger Causality Test, one way causal relationship is found between the currencies such as Indian Rupees, Japanese Yen, Pound Sterling, and US Dollar and the imports. The results of Johansen Co-integration Test vividly ensure the long run equilibrium relationship of the variables and the movement of all the variables together in the long run equilibrium. Paradox is recommended to be named as Import Paradox of Pound- Dollar. The structural breakpoint is found in year 2009 which is the year of cease-fire in Sri Lanka.
Keywords: exchange rate; imports; multiple regression; granger cause; johansen cointegration